Optimising User Interface (UI) and User Experience (UX) on E-Commerce Platforms to Improve Customer Retention - Diana Novita; Hanifah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Fierce competition in the world of e-commerce requires platforms not only to attract new customers but also to retain existing ones in a highly dynamic digital market. Customer retention, defined as a business’s ability to maintain customer loyalty over a specific period of time, has become a vital metric for long-term business sustainability. As consumers are increasingly exposed to multiple shopping alternatives, e-commerce platforms must ensure that their digital environment remains engaging, efficient, and user-friendly. This study highlights the crucial role of User Interface (UI) and User Experience (UX) as key determinants that influence customer behaviour and significantly contribute to improving retention rates. Using a combination of literature review and case study methodology, this journal identifies several essential UI/UX elements that directly impact user satisfaction. These elements include clean and visually appealing interface design, intuitive and predictable navigation paths, fast loading speed, and a seamless, simplified checkout process. Each of these components plays a strategic role in reducing user frustration, increasing convenience, and fostering trust in the platform. When users are able to browse, search, and complete transactions effortlessly, their likelihood of revisiting the same platform increases significantly. The analysis shows that a smooth, personalised, and efficient overall user experience has a positive correlation with repeat purchases and higher customer loyalty. Therefore, the study concludes that investing in UI/UX design is not merely an operational cost but a fundamental business strategy for building long-term customer relationships and achieving stable growth in an increasingly competitive e-commerce environment. This journal recommends that e-commerce businesses prioritise UI/UX development within their operational strategies to enhance customer satisfaction and strengthen long-term retention.